A highly sensitive colorimetric approach based on tris (bipyridine) Ruthenium (II/III) mediator for the enzymatic detection of phenylalanine - Messina, Maria Anna; Maugeri, Ludovica; Forte, Giuseppe; Ruggieri, Martino; Petralia, Salvatore (Frontiers in Chemistry, 2023)
The accurate monitoring of phenylalanine concentration plays a prominent role in the treatment of phenylketonuria (PKU). In this study, we present an enzymatic assay based on Phenylalanine Dehydrogenase/NAD+ and tris (bipyridine) Ruthenium (II/III) as a colorimetric mediator for the detection of Phenylalanine concentration. The amount of amino acid was quantitatively recognized by optical absorption measurements at 452 nm through the conversion of Ru (byp)33+ to Ru (byp)32+, which is induced by the neoformed NADH. A detection limit of 0.33 µM, a limit of quantification of 1.01 µM, and a sensitivity of 36.6 a.u nM−1 were obtained. The proposed method was successfully tested using biological specimens from patients affected by hyperphenylalaninemia. The proposed enzymatic assay showed a high selectivity, making it a promising alternative for the development of versatile assays for the detection of phenylalanine in diluted serums.